Cloud Computing And Virtualization: Trends And Technologies (International Journal of Engineering and Computer Science, 2014)
In our world today, the inculcation of ICT in government and business has become an indispensable tool in the implementation of  government’s policies and also for businesses to tap into the realms of competiveness. Previous studies have proved the ubiquitous of ICT to be one of the efficient and effective way in realizing this phenomenon. A contemporary technology in recent times is cloud computing; whose aim is to deliver the utility of ICT in a cost efficient and effective manner. It adopts the technique of elasticity that rides on the principle of “pay as you need”, which prevents redundancies and allows for scalability and much more diversity in the use of resources. This paper aims at reviewing the provision of the cloud computing capabilities and the constraints that comes with it.